2021
DOI: 10.1002/cctc.202100248
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Catalyzed Hydrogen Evolution Reactions Involving Strong C−H Bonds Activation via Hydrogen Atom Transfer

Abstract: Hydrogen evolution reactions have been proved to be a powerful and green strategy in organic synthesis. Differing from hydrogen evolution reactions catalyzed by noble metal pincer complex with some limitations, the reactions facilitated by merging hydrogen atom transfer (HAT) and metal‐catalyzed hydrogen evolution (MCHE) represents a more attractive and promising alternative for direct formation of chemical bonds from available feedstocks in synthetic chemistry. Given the significance, this review summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…However, stoichiometric oxidants are generally required, which results in a diminished atom economy of the overall process with unwanted waste generation and poor functional group compatibility. Over the past decade, a greener approach involving CDC reactions with hydrogen evolution in the absence of any external oxidants has been achieved through transition metal catalysis, , photoredox/cobalt dual catalysis, quantum dot photocatalysis, and electrocatalysis. ,, Although the strategy of hydrogen-evolution cross coupling of C­(sp 3 )–H bonds has gained significant momentum, such approaches have several limitations, including a reliance on transition metal catalysts or specialized electrochemical equipment. Therefore, the development of new strategies of hydrogen-evolution cross coupling with readily available C­(sp 3 )–H feedstocks in a metal-free and operationally simple manner is highly desirable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, stoichiometric oxidants are generally required, which results in a diminished atom economy of the overall process with unwanted waste generation and poor functional group compatibility. Over the past decade, a greener approach involving CDC reactions with hydrogen evolution in the absence of any external oxidants has been achieved through transition metal catalysis, , photoredox/cobalt dual catalysis, quantum dot photocatalysis, and electrocatalysis. ,, Although the strategy of hydrogen-evolution cross coupling of C­(sp 3 )–H bonds has gained significant momentum, such approaches have several limitations, including a reliance on transition metal catalysts or specialized electrochemical equipment. Therefore, the development of new strategies of hydrogen-evolution cross coupling with readily available C­(sp 3 )–H feedstocks in a metal-free and operationally simple manner is highly desirable.…”
mentioning
confidence: 99%
“…Our investigation of the conditions indicated that a catalytic amount of mesityl-10-methylacridinium perchlorate (Mes-Acr + ClO 4 – ) and Co­(dmgh) 2 PyCl in the presence of two equivalents of diphenyl phosphate in acetonitrile at 60 °C under blue LED light (475 nm, 36 W) irradiation for 24 h gave desired coupling product 3 in 87% yield (Table , entry 1). Unexpectedly, an improved product yield (95%) was obtained using 1,2-dichloroethane (DCE) as the solvent even in the absence of cobalt catalyst, which was essential in the existing reported hydrogen evolution dehydrogenative couplings , (entry 2). Hydrogen gas was detected as the coupled product (Figure S4).…”
mentioning
confidence: 99%
See 1 more Smart Citation